Handbook of Metalloproteins 2004
DOI: 10.1002/0470028637.met278
|View full text |Cite
|
Sign up to set email alerts
|

The Organomercurial LyaseMerB

Abstract: Mercury is introduced into the environment either from natural occurrences or from human activities, and consumption of mercury‐contaminated fish poses a serious human health issue. The three inorganic forms of mercury are elemental mercury, mercurous compounds, and mercuric compounds, while the most abundant organic form is methylmercury. Owing to its ability to permeate membranes and accumulate in organisms, methylmercury is more toxic than ionic mercury. Mercury‐resistant bacteria have developed a two enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…(RC607) MerB2, and Clostridium butyricum MerB2) carry a Ser residue instead of Asp in their catalytic triad. Significantly, recent studies showed that the presence of a Ser residue in the active site substantially reduces the catalytic activity as well as the substrate specificity of these four MerB2 variants. However, the mechanism by which these serine-containing organomercurial lyases (MerB2) cleave the Hg–C bonds of organomercurials has not been studied yet. In this context, therefore, it is beneficial to develop chemistry between [S 2 ]-donor ligands with various MeHg + compounds (such as ionic [MeHg]­BF 4 , MeHgCl, and MeHgI) which may help in understanding the mechanism of detoxification of MeHg + by microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…(RC607) MerB2, and Clostridium butyricum MerB2) carry a Ser residue instead of Asp in their catalytic triad. Significantly, recent studies showed that the presence of a Ser residue in the active site substantially reduces the catalytic activity as well as the substrate specificity of these four MerB2 variants. However, the mechanism by which these serine-containing organomercurial lyases (MerB2) cleave the Hg–C bonds of organomercurials has not been studied yet. In this context, therefore, it is beneficial to develop chemistry between [S 2 ]-donor ligands with various MeHg + compounds (such as ionic [MeHg]­BF 4 , MeHgCl, and MeHgI) which may help in understanding the mechanism of detoxification of MeHg + by microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The key catalytic roles for C96, C159, and D99 are supported by the fact that the two cysteine residues are conserved in all known variants of MerB and the aspartic acid is conserved in all but four of the known variants [ Bacillus megaterium MerB2, Bacillus subtillis MerB2, Bacillus sp. (RC607) MerB2, and Clostridium butyricum MerB2], in which the D99 is replaced with a serine residue . Although these four serine-containing MerB variants are derived from different organisms, they have 100% amino acid sequence identity so they are in fact identical proteins.…”
mentioning
confidence: 99%
“…46 In these four strains, the bacteria express two MerB proteins from their mer operon. The first, designated MerB1, contains the three catalytic residues corresponding to C96, D99, and C159 in E. coli MerB, but the second, designated MerB2, contains a serine residue in the position of the aspartic acid residue (D99), in addition to the two cysteine residues.…”
Section: Discussionmentioning
confidence: 99%